Konsepsi Alquran Tentang Harta Gono Gini dalam Rumah Tangga Muslim - Gani, Erman; Wijaya, Nadiah Azizah Arisa; Budiman, Arif (MUI Kota Pekanbaru, 2024)
Marriage is the sunnah of the Apostle and worship for everyone who is ready and physically and mentally capable. The principle of marriage is to form a family or household that is sakinah mawaddah warahmah. There are several things that must be maintained together in a marriage, one of which is property. The continuity of life in a marriage requires property. Islam explains that the husband is obliged to meet the needs of the household but in today's modern life, the wife's role is not only to serve her husband and take care of children, but has also played a role in helping her family's economy and has an economic job. Whereas the obligation to earn a living is only imposed on the husband who is the backbone of the family. This article aims to examine how the Quran explains the position of jointly acquired property (gono gini) in the household, although the Quran explains it specifically. Basically, this paper is qualitative in nature because the working instrument is library research. All data is in the form of written library materials, including books/books, research reports, papers, scientific journals, inertenet data and others. This research explains that in the perspective of the Koran, there are no strict rules regarding joint property in the household. Scholars have different opinions about joint property. The first opinion says Islam does not recognize the existence of joint property except by shirkah. Meanwhile, another opinion states that the occurrence of marriage is considered a shirkah between the husband and wife. However, in Indonesian Islamic law, joint property is explained in Article 35 of the Marriage Law and Articles 85-97 of the Compilation of Islamic Law (KHI). Husband and wife have full rights to perform legal actions on each other's property, such as grants, charity, or others. However, a husband or wife is not allowed to sell or transfer joint property without the consent of one of the parties.